EVALUASI KINERJA HEAT EXCHANGER 260E-103 PADA KILANG LUBE OIL COMPLEX III UNIT 260 PT KILANG PERTAMINA INTERNASIONAL RU IV CILACAP - Villia Rian Ashari; welayaturromadhona, welayaturromadhona (Petroleum Engineering, Faculty of Engineering, University of Jember, 2024)
In the process of processing petroleum, PT Pertamina International RU IV Cilacap is equipped with a heat exchanger asa supporting tool for the production and processing. Heat exchanger functions as a heat exchange that works with theprinciple of heat exchange without mass transfer. The use of heat exchangers that are in extreme environments and areused for a long period of time to pass fluids, there is a high probability of deposit formation or impurities that can affectthe pressure drop and decrease the performance efficiency of the heat exchanger in terms of heat exchange. Planning forcleaning must be considered to maintain the performance of the heat exchanger performance so that it remains in optimalcondition. The heat exchanger that will be evaluated in this study is Heat Exchanger 260E-103 at PT PertaminaInternational RU IV Cilacap. The research was conducted using quantitative methods through the calculation of foulingfactor, pressure drop, and heat transfer efficiency. The results showed that the Rd value of Heat Exchanger 260E-103 ofLMO was 0.0317 hr ft2 oF/Btu; 0.0058 hr ft2 oF/Btu; 0.0048 hr ft2 oF/Btu, MMO was 0.0193 hr ft2 oF/Btu; 0.0157 hr ft2oF/Btu; 0.0070 hr ft2 oF/Btu, and DAO of 0.0153 hr ft2 oF/Btu; 0.0193 hr ft2 oF/Btu; 0.0029 hr ft2 oF/Btu. The pressuredrop value of Heat Exchanger 260E-103 of LMO is 12.021 Psi; 10.632 Psi; 10.416 Psi, MMO is 11.077 Psi; 11.108 Psi;10.435 Psi, and DAO is 14.149 Psi; 13.764 Psi; 13.625 Psi. The efficiency for Heat Exchanger 260E-103 of LMO is22.81%; 79.47%; 82.16%, MMO is 29.07%; 46.03%; 72.16%, and DAO is 17.43%; 60.06%; 45.04%. The results showthat Heat Exchanger 260E-103 is not suitable for use because it has Rd and pressure drop values exceeding normallimits, and efficiency is below standard.